(untitled) (Biological Sciences - PJSIR, 2022)
The experiment was conducted to determine drought tolerance of wheat genotypes under water stress conditions at Botanical Garden, Department of Plant Breeding and Genetics, Sindh Agriculture University, Tandojam during 2017-2018. The experiment was laid out in split plot design with three replications. Two irrigation regimes i.e. non-stress and water stress were considered as main plots and genotypes as sub-plots. The mean squares from analysis of variances showed that treatments were significant for most of the traits yet genotypes were significant for all the traits such as spike length, grains/spike, seed index, grain yield/plant, biological yield/plant and harvest index. Treatment x genotype interactions was also significant for most of the traits except spike/length. In non-stress, Marvi, TD-1, Kiran-95 and TJ-83 recorded higher mean performance for spike length, grains/spike, seed index, grain yield/plant, biological yield/plant and harvest index, while in water stress conditions, generally genotypes like TD-1, TJ-83, NIA-Sundar, Kiran-95 and Galaxy recorded higher mean values for spike length, grains spike, seed index, grain yield/plant, biological yield/plant and harvest index. The wheat genotypes like NIA-Sunder, TJ-83, Galaxy and Benazir recorded minimum reductions for majority of the traits, thus proved their water stress tolerance. The correlation coefficient revealed that in stress conditions, grain yield was significantly and positively associated with number of grains/spike (r = 0.62*), seed index (r = 0.48*), biological yield/plant (r = 0.91**) and harvest index (r = 0.80**). High heritability estimates were recorded in non- stress (ranged from h2=84.50 to 99.10%) as well as in water stress (ranged from h2= 88.28 to 98.22%) for all the studied traits. On the basis of minimum reductions in water stress, the genotypes such as NIA- Sunder, TJ-83, Galaxy and Benazir were considered as drought tolerant hence they could be grown in water stress environment.